A survey of pharmacists' roles in gastroenterology and hepatology. Issue 10 (11th July 2021) - Choi, David; Patel, Shivani; Trivedi, Itishree; Rubin, David T.; Moss, Alan; Bhat, Shubha
Abstract: Introduction: Pharmacists' roles have evolved over time to include direct patient care and optimization of medication related outcomes. However, one therapeutic area lacking an evaluation of pharmacist involvement is gastroenterology and hepatology (GI/liver). This area utilizes biologics and other treatment options with considerable cost and safety, thus pharmacists can have a significant impact in caring for patients with GI/liver conditions. Objectives: Identify the background training of pharmacists practicing in GI/liver and characterize their current practice landscape. Methods: A survey was developed and disseminated through the American College of Clinical Pharmacy (ACCP) GI/Liver/Nutrition and Ambulatory Practice and Research Networks (PRN) groups and through the American Society of Health System Pharmacists (ASHP) Section of Specialty Pharmacy Practitioners from November 30, 2020 to January 16, 2021. Results: Of 42 unique responses received, respondents primarily practiced at an academic medical center in the ambulatory setting. Although respondents reported completing various types of post‐graduate training (residency and fellowship), 55% of respondents endorsed prior exposure to GI/liver during training. Common disease states managed were inflammatory bowel disease, hepatitis B and C, and cirrhosis. Half of respondents reported having a collaborative practice agreement and 67% reported independently seeing patients in clinic, developing therapy plans, and ordering/monitoring labs. Approximately 69% do not have dedicated time for research. Only 23% of respondents reported billing for clinical services. Conclusion: In this survey, pharmacists are involved in caring for patients with GI/liver conditions under collaborative practice agreements and primarily based in an outpatient clinic. Future growth of pharmacists in this therapeutic space will require increased formalized training of GI/liver conditions and strategies to optimize reimbursement.